KAJAO LALIDDONG PESAN-PESAN DALAM PENGEMBANGAN KERAJAAN BONE - Ummul Khair; Rahmawati (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2023)
This research examines Kajao Laliddong, messages in the development of the Bone Kingdom. The main topic of discussion is "How are the Messages of Kajao Laliddong in the development of the Bone kingdom."? The main problem is described in the formulation of the problem, namely; What was the condition of the Bone Kingdom before the emergence of Kajao Laliddong in the 16th Century? What are the messages and implications of Kajao Laliddong's thoughts in developing the kingdom of Bone? This research is library research using historical and anthropological research approaches because all data sources used are in written form, this can be obtained through library research, document study, and described qualitatively. Processing the data using content analysis (content analysis) with an interdisciplinary approach. The results of this study indicate that; 1) the condition of the Bone Kingdom in the XVI century before the emergence of Kajao Laliddong can be seen in its government structure. The terms often used include Arungpone (mangkau/king), Tomarilaleng (Prime Minister), Makkedangnge tana (Minister of Foreign Affairs), Ade Pitue (Seven Traditional Institutions), Punggawa (warlord), Jennang (supervisor), Bissue (person holy). 2) Kajao Laliddong is the title given by the king of Bone to La Mellong, he was born in 1507 and died in 1586 for his brilliance in developing Bone society with his clear written advice. Kajao Laliddong's advice during his lifetime for the Bone kingdom was written in the Lontara Manuscript, these values cover three aspects, namely the first aspect of education which is focused on 9 value points namely the values of Lempue, ade', siri'e, awaraningeng, acca, assitinajang, getteng, reso and appesona ri Dewata Seuwae. As for the second aspect, namely the social community and the three political aspects conveyed by Kajao Laliddong, the first is ade, talk, rapang and wari. The main element of Kajao Laliddong's thought in his time was considered as a thinker as well as a wise figure who could guide society individually and the general public in the kingdom of Bone. Adaptation of behavior that leads to adab actions that are in line with every era.